Menjaring Karakter Emas: Strategi Kepemimpinan Spiritual Kepala Sekolah dalam Menginternalisasi Nilai-nilai Islam dan Membangun Ekosistem Religius Holistik di Sekolah Dasar Islam - Zein, Nur Asiah; Muhammad Soffian hadi; Niswah Zahrotul jannah; Achda Fitriah (Jurnal Penelitian dan Penilaian Pendidikan, 2025)
Background: Strengthening religious character at the elementary level requires a leadership strategy that is not merely managerial but spiritually grounded. The Principal, acting as a Spiritual Leader, plays a crucial role in creating a school environment that consistently reflects Islamic values. Purpose: This study aims to analyze the strategies employed by the Principal of SD Islam Al Azhar 15 Pamulang in internalizing Islamic values and building a Holistic Religious Ecosystem to shape students' character. Methods: A qualitative research design with a case study approach. Research subjects include the principal, teachers, and parent representatives. Data collection techniques involved in-depth interviews, participant observation, and school program document analysis. Results and Discussion: The strategies identified include Modeling (daily role modeling), Coaching (continuous spiritual mentoring), and Integrative Curriculum Design. The implementation of these strategies successfully mobilized the participation of all stakeholders to create the school ecosystem as a center for character development. Research Contribution: This study provides a theoretical contribution regarding an effective Spiritual Leadership model for Principals as the primary key in the development of religious character in Islamic basic education institutions.Latar Belakang: Penguatan karakter religius pada jenjang sekolah dasar memerlukan strategi kepemimpinan yang lebih dari sekadar manajerial, tetapi berlandaskan spiritual. Kepala sekolah sebagai Pemimpin Spiritual memiliki peran krusial dalam menciptakan lingkungan sekolah yang secara konsisten merefleksikan nilai-nilai Islam. Tujuan: Penelitian ini bertujuan menganalisis strategi Kepala Sekolah SD Islam Al Azhar 15 Pamulang dalam menginternalisasi nilai-nilai Islam dan membangun Ekosistem Religius Holistik untuk membentuk karakter siswa. Metode: Penelitian kualitatif dengan pendekatan studi kasus (case study). Subjek penelitian adalah kepala sekolah, guru, dan perwakilan orang tua. Teknik pengumpulan data menggunakan wawancara mendalam, observasi partisipatif, dan analisis dokumen program sekolah. Hasil dan Pembahasan: Strategi yang ditemukan meliputi Modeling (keteladanan sehari-hari), Coaching (pendampingan spiritual berkelanjutan), dan Integrative Curriculum Design. Implementasi strategi ini berhasil menggerakkan partisipasi seluruh stakeholder untuk menciptakan ekosistem sekolah sebagai pusat pengembangan karakter. Kontribusi Penelitian: Penelitian ini memberikan kontribusi teoretis mengenai model Kepemimpinan Spiritual Kepala Sekolah yang efektif sebagai kunci utama dalam pengembangan karakter religius pada lembaga pendidikan Islam dasar.